2022
DOI: 10.1111/rec.13759
|View full text |Cite
|
Sign up to set email alerts
|

Granivorous ants prefer small and unprotected seeds—implications for restoration in arid ecosystems

Abstract: Successful seed-based restoration in dryland systems is difficult due to the many limitations associated with germination and establishment. Seed predators, including granivorous ants, can consume or move applied seeds offsite reducing restoration success. Granivorous ants in the U.S. southwest move and store tens of thousands of seeds and show preferences for seeds based on weight, size, nutrient content, and novelty. In this study, we examine which seed traits most influence seed predation rates in a grassla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Morphology is another common driver of seed preference, and the ACHY and HEAN seeds preferred by P. occidentalis are morphologically similar, with smooth, awnless seed coats. This result supports recent studies that find lower ant granivory for seeds with a structure or coating (Crist & MacMahon 1992;Paolini et al 2020;Wandrag et al 2021) or a higher seed to seed plus structure ratio (Martyn et al 2022), possibly because large awns make seeds cumbersome for transport. In contrast, an older study by Pulliam and Brand (1975) found that Pogonomyrmex spp.…”
Section: Seed Preferencesupporting
confidence: 91%
See 1 more Smart Citation
“…Morphology is another common driver of seed preference, and the ACHY and HEAN seeds preferred by P. occidentalis are morphologically similar, with smooth, awnless seed coats. This result supports recent studies that find lower ant granivory for seeds with a structure or coating (Crist & MacMahon 1992;Paolini et al 2020;Wandrag et al 2021) or a higher seed to seed plus structure ratio (Martyn et al 2022), possibly because large awns make seeds cumbersome for transport. In contrast, an older study by Pulliam and Brand (1975) found that Pogonomyrmex spp.…”
Section: Seed Preferencesupporting
confidence: 91%
“…Similarly, Kerley and Whitford (2000) found that the functional importance of harvester ants as granivores increased as overgrazing shifted the vegetation community in the Chihuahuan desert. In addition, studies that consider granivores as a biotic filter to restoration consistently find significant influences of both ants and rodents (Gurney et al 2015; Fick et al 2016; Martyn et al 2022). Given the potential of harvester ants to influence restoration outcomes, and the likelihood that ant nest colony density and behavior is altered in degraded areas, we need a deeper understanding of harvester ant impacts to restoration approaches on overgrazed grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…However, disturbance reduced soil nitrate in our early successional communities in the peak growing season (June and July), which could plausibly be the explanation for the negative effect of disturbance on colonist cover in early succession. Disturbance may have facilitated higher rates of seed predation and herbivory too (Korell et al, 2017; MacDougall & Wilson, 2007; Martyn et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Any increase in soil organic matter would have significant ecosystem benefits. Furthermore, we know seed predation is an underappreciated factor in plant establishment, 37 and we know litter depth influences habitat selection of seed-eating small mammals. 38 How do pits influence the rate of seed predation in restoration plantings?…”
Section: Soil Pitting In the Context Of The Broader Environmentmentioning
confidence: 99%